AN ANTHOLOGY OF OUTSTANDING ACHIEVEMENTS IN SCIENCE AND TECHNOLOGY. PART 12: CLASSICAL ELECTRODYNAMICS - M.I. Baranov (National Technical University "Kharkiv Polytechnic Institute", 2013)
A brief scientific essay on the history of classical electrodynamics development in the 18th through 20th centuries is given.